Metal and metal oxide nanoparticles from Mimusops elengi Linn. Extract : green synthesis, antioxidant activity, and cytotoxicity - Selly Arvinda Rakhman,; Tanyarath Utaipan,; Charoen Pakhathirathien,; Weeraya Khummueng, (Penerbit Universiti Kebangsaan Malaysia, 2022)
In this study, both silver (Ag) and zinc oxide (ZnO) nanoparticles are green synthesized using a water extract of the Mimusops elengi Linn. leaf. The methods are simple, inexpensive, nontoxic, and eco-friendly. The AgNPs and ZnONPs are formed using phytochemical substances in M. elengi leaf extract at room temperature. The phenolics and flavonoids in the leaf extract is the key compounds that act as the metal-reducing agents. The effective parameters of the green synthesis (the metal concentration, leaf extract concentration, pH, temperature, and reaction time) are evaluated. The formation of the metal and metal oxide nanoparticles (NPs) are confirmed through colour change visuals, ultraviolet–visible (UV-vis) spectroscopy (UV-vis), and Fourier transform infrared (FTIR) spectroscopy. The morphological and crystalline characterizations of the NPs are established using transmission electron microscopy (TEM) and X-ray diffraction (XRD). The TEM results indicated that the AgNPs are predominantly spherical in shape with an average particle size of 22.12 nm. The ZnONPs have mostly rod-like morphology with an average size of 28.44 nm. The antioxidant activity and cytotoxicity of the synthesized NPs against colon cancer cells (Caco-2 cells) are evaluated; the obtained NPs exhibited good free radical scavenging activity through DPPH, ABTS, and FRAP assays. The cytotoxicity results demonstrated that only the 2,000-ppm extract had any potential against the Caco-2 cells; both the AgNPs and ZnONPs had no effect on Caco-2 cells. However, regarding human health, metal NPs are safe to use and are useful in the other applications.